Formalising triage in general practice towards a more equitable, safe, and efficient allocation of resources. (24th May 2022) - Rodrigues, Daniela; Kreif, Noemi; Saravanakumar, Kavitha; Delaney, Brendan; Barahona, Mauricio; Mayer, Erik
Abstract : Daniela Rodrigues and colleagues argue that triage of all patient requests in general practice could help practices managing demand with limited resources